Learning with Mobiles in the Digital Age - John Traxler (Charles University, 2018)
Personal mobile devices are central to the current digital age, and will soon be pervasive and ubiquitous, and unremarkable in most of the world's societies and cultures. They are central to the educational futures for the digital age, to both in theory and practice. They are, however, not straightforward. Whilst the relationships of these technologies to formal education and its professions and institutions, conceptualised as 'mobile learning', seemed straightforward, it has also become increasingly marginal and irrelevant whilst the relationship between mobile devices and society outside formal education is increasingly problematising the nature, role and purpose of both education and learning. This article explores this tension; it characterises and conceptualises it in terms of competing paradigms.